Transient receptor potential vanilloid 2 function regulates cardiac hypertrophy via stretch-induced activation. Issue 3 (March 2017) - Koch, Sheryl E.; Mann, Adrien; Jones, Shannon; Robbins, Nathan; Alkhattabi, Abdullah; Worley, Mariah C.; Gao, Xu; Lasko-Roiniotis, Valerie M.; Karani, Rajiv; Fulford, Logan; Jiang, Min; Nieman, Michelle; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Hypertension (increased afterload) results in cardiomyocyte hypertrophy leading to left ventricular hypertrophy and subsequently, heart failure with preserved ejection fraction. This study was performed to test the hypothesis that transient receptor potential vanilloid 2 subtype (TRPV2) function regulates hypertrophy under increased afterload conditions. Methods: We used functional (pore specific) TRPV2 knockout mice to evaluate the effects of increased afterload–induced stretch on cardiac size and function via transverse aortic constriction (TAC) as well as hypertrophic stimuli including adrenergic and angiotensin stimulation via subcutaneous pumps. Wild-type animals served as control for all experiments. Expression and localization of TRPV2 was investigated in wild-type cardiac samples. Changes in cardiac function were measured in vivo via echocardiography and invasive catheterization. Molecular changes, including protein and real-time PCR markers of hypertrophy, were measured in addition to myocyte size. Results: TRPV2 is significantly upregulated in wild-type mice after TAC, though not in response to beta-adrenergic or angiotensin stimulation. TAC-induced stretch stimulus caused an upregulation of TRPV2 in the sarcolemmal membrane. The absence of functional TRPV2 resulted in significantly reduced left ventricular hypertrophy after TAC, though not in response to beta-adrenergic or angiotensin stimulation. The decreased development of hypertrophy was not associated with significant deterioration of cardiac function. Conclusion: We conclude that TRPV2 function, as a stretch-activated channel, regulates the development of cardiomyocyte hypertrophy in response to increased afterload.